Experimental methods for ultrasonic testing of complex-shaped parts encased in ice. (April 2019) - Simonetti, F.; Fox, M.
Abstract: Detection of damage in safety-critical components with complex geometry represents a long-standing challenge in NDE. The ultrasonic inspection of these parts in immersion is often not feasible due to the large impedance and velocity contrast between water and metals which can severely limit the penetration of the ultrasonic signal inside the part. However, this contrast can be significantly reduced if the water is frozen prior to the inspection leading to what has been referred to as Cryoultrasonic NDE. Since the speed of longitudinal waves in ice is more than 2.5 times greater than the speed in water, ice can be an ideal solid couplant provided that it is devoid of bubbles and cracks and that it is fully bonded to the surface of the part. This paper introduces new experimental methods to encase complex parts in blocks of crystal clear ice and presents the first low temperature scanner for ultrasonic array testing of ice-encapsulated parts. It is shown that by controlling the propagation of the solidification front while water is freezing, it is possible to prevent the formation of cracks inside the ice volume. On the other hand, bubble nucleation can be avoided by continuously forcing water circulation on the solidification front. An analytical model is provided to describe the propagation of the front and predict freezing times. Moreover, high-frequency ultrasonic monitoring experiments confirm the excellent adhesion strength properties of ice to metals. Finally, experiments performed with an additively manufactured Ti6Al4V impeller demonstrate the feasibility of performing low temperature array contact scans on the surface of the ice block encasing the part.